Macular pigment optical density of hyperopic anisometropic amblyopic patients measured by fundus reflectometry - Wang, Chenxiao; Yu, Jinjin; Pan, Mengmeng; Ye, Xiuhong; Song, E. (Frontiers in Medicine, 2022)
Purpose Hyperopic anisometropia is a major cause of amblyopia and may be associated with macular pigment optical density (MPOD) reduction. To explore whether the MPOD changes in hyperopic anisometropic amblyopia, we measured the MPOD using fundus reflectometry in eyes with hyperopic anisometropic amblyopia and normal vision. Methods This was a cross-sectional study conducted from January 2017 to June 2017. Forty subjects (25 males and 15 females) between the ages of 6 and 10 years were recruited. The subjects' eyes were divided into two groups: amblyopic eyes (best-corrected visual acuity (BCVA) not more than 20/25 or BCVA of two eyes differing by two or more lines) and fellow eyes. All enrolled subjects underwent a comprehensive ophthalmic examination, including extraocular motility assessment, cover-uncover testing, and refractive error (noncycloplegic), BCVA, axial length (AL), macular foveal thickness (MFT) and MPOD (Visucam® 200, Carl Zeiss Meditec AG, Germany). Results The MPOD of amblyopic and fellow eyes was 0.12 ± 0.03 log units and 0.13 ± 0.04 log units, respectively, with a significant difference (P = 0.026). The MFT of amblyopic and fellow eyes was 241.28 ± 13.95 and 237.13 ± 16.02 μm, respectively, revealing that the MFT was significantly higher in amblyopic eyes than in fellow eyes (P = 0.028). Conversely, there was no correlation between the MPOD and MFT in the two groups. Conclusions This study is the first to report that the MPOD is decreased in hyperopic anisometropic amblyopia. In this study, no correlation between the MPOD and MFT was found. In the future, factors that induce a decrease in the MPOD in eyes with hyperopic anisometropic amblyopia should be explored in a large-sample study with follow-up observation.